Meeting WASH SDG6: insights from everyday practices in Dar es Salaam. (April 2021) - Hofmann, Pascale
While existing datasets and statistics provide a useful indication of progress towards meeting Sustainable Development Goal (SDG) 6, they are far from accurate and sufficient. There is a need for new and more disaggregated data to shed light on unequal service provision patterns, particularly for many informal urban settlements. This paper aims to address this need through a granular space and time-based examination of the diverse everyday practices in two lower-income settlements of Dar es Salaam. The findings reveal spatial and temporal variations at the inter- and intra-settlement scale while tracing differential and changing practices among poor women and men. The in-depth case study exposes important blind spots in policy and planning, provides wider lessons for achieving more equal and sustainable access to services and developing more responsive policy and planning approaches, and emphasizes the value of local data collection.